2021
DOI: 10.1002/pc.26097
|View full text |Cite
|
Sign up to set email alerts
|

Optimized selection of nanohydroxyapatite‐filled dental restorative composites formulation for best physico‐mechanical, chemical, and thermal properties using hybrid analytical hierarchy processmulti‐objective optimization on the basis of ratio analysis approach

Abstract: The present research explored and optimized dental restorative composite (DRC) materials filled with nanohydroxyapatite (n-HAP) based on their physico-mechanical, chemical, and thermal properties. In the same context, hybrid analytical hierarchy process (AHP) and multi-objective optimization on the basis of ratio analysis (MOORA) approach was proposed to select the best DRC with optimal combination of physico-mechanical, chemical, and thermal properties. Seven formulations based on Bis-GMA as a base monomer wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The combination of these base and diluent monomers has been extensively investigated to improve the mechanical and physical properties of the composites and contribute to extending the dental material industry. A systematic investigation of material property prediction models has been developed to optimize input parameters such as weight fraction and concentration of monomers [67][68][69] and fillers [70]. To date, there are two major types of DRCs classified according to handling characteristics: flowable and packable materials.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…The combination of these base and diluent monomers has been extensively investigated to improve the mechanical and physical properties of the composites and contribute to extending the dental material industry. A systematic investigation of material property prediction models has been developed to optimize input parameters such as weight fraction and concentration of monomers [67][68][69] and fillers [70]. To date, there are two major types of DRCs classified according to handling characteristics: flowable and packable materials.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…It provides a high degree of crystalline nature and structural stability to the polymer matrix, which makes it more attractive. [12,13] The high viscosity of UHMWPE when mixed with filler materials results in the clustering of filler materials, which increases void and defects in composite materials. [14] Finally, biocomposite materials have low mechanical strength.…”
Section: Introductionmentioning
confidence: 99%
“…MOORA technique was used to determine the process parameters like pulse on time, voltage and wire feed rate, metal removal rate and surface roughness for aluminium (A6061) reinforced zinc oxide particle metal matrix (Sadhasivam et al, 2021). Alternative approach of response surface method of experimental design was also used for optimisation (Gangwar et al, 2021;Patil, 2017). It has been observed that researchers focused over optimising fracture toughness and other properties in the field of material science.…”
Section: Introductionmentioning
confidence: 99%